2023
DOI: 10.1007/s00134-023-07138-0
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-associated acute kidney injury in the intensive care unit: incidence, patient characteristics, timing, trajectory, treatment, and associated outcomes. A multicenter, observational study

Abstract: Purpose The Acute Disease Quality Initiative (ADQI) Workgroup recently released a consensus definition of sepsis-associated acute kidney injury (SA-AKI), combining Sepsis-3 and Kidney Disease Improving Global Outcomes (KDIGO) AKI criteria. This study aims to describe the epidemiology of SA-AKI. Methods This is a retrospective cohort study carried out in 12 intensive care units (ICUs) from 2015 to 2021. We studied the incidence, patient characteristics, timing, trajector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Among the three standards, high PRISM scores and elevated PCT level were independent risk factors for SA-AKI. KDIGO had more independent risk factors, which is consistent with similar research ( 21 , 22 ). The PRISM score is currently the most widely used assessment scale in the PICU and shows good ability to predict the severity and mortality risk of critically ill children ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…Among the three standards, high PRISM scores and elevated PCT level were independent risk factors for SA-AKI. KDIGO had more independent risk factors, which is consistent with similar research ( 21 , 22 ). The PRISM score is currently the most widely used assessment scale in the PICU and shows good ability to predict the severity and mortality risk of critically ill children ( 21 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, this may indicate that FA in the presence of AKI has more of an impact on renal recovery than FA before the onset of AKI. Thus, patients with FA and severe AKI should be considered especially “at risk” for a delayed or no renal recovery that is associated with end-stage renal disease and dialysis-dependency [ 32 , 42 , 43 ] as well as higher mortality [ 32 , 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since no urine output values were available for our patient cohort, AKI definition was based on creatinine values alone. However, a recent study in patients with sepsis-associated AKI showed a better prognosis regarding renal recovery and mortality in patients with AKI diagnosed by low urine output alone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] It is now evident that both sepsis and SA-AKI are a mixture of syndromes in which the cause and the response of the host play an important role in creating specific endotypes with peculiar characteristics and clinical pictures. [27–29] For this reason, it seems unlikely to foresee a positive response to a therapy of the overall studied population, especially in light of the different pathophysiological mechanisms involved.…”
Section: The Case Of the Critically Ill Patient With Sepsis Or Sa-akimentioning
confidence: 99%